Spectrum of parasitic infections on fine-needle aspiration cytology presenting as superficial nodules: A retrospective study of 5 years in a tertiary care hospital - Zini Chaurasia,; Swapnil Agarwal,; Renu Gupta,; Cheta Singh,; Surbhi Jani, (Asian Journal of Medical Sciences, 2023)
Background: Parasitic infestations are very common in a developing nation like India. They may present as superficial nodules and are often either missed or misdiagnosed as other soft-tissue lesions. Fine-needle aspiration cytology (FNAC) is an easy, minimally invasive technique to detect, and diagnose these lesions. Parasitic infections are present in every age group with cysticercosis being the most common parasitic infestation. The present study highlights the role of cytology in diagnosing parasitic lesions and also analyzes the spectrum of these lesions in a tertiary care hospital. Aims and Objectives: This study was carried out to assess the spectrum of parasitic infestations in a tertiary care hospital of North West Delhi over 5 years (2015–2019). This was a retrospective and descriptive study done in the Department of Pathology, Dr. BSA Hospital, Delhi. Materials and Methods: Sixty-six cases out of a total of 15094 FNACs performed over 5 years (2015–2019) that were diagnosed as parasitic lesions on FNAC were included in our study. The records were retrieved, analyzed, and recorded. Clinical details were obtained from the FNAC requisition slips. Results: A total of 66/15094 FNACs conducted over 5 years were diagnosed as parasitic lesions. Fifty-seven cases of cysticercosis, six cases of filariasis, two cases of echinococcosis, and one case of toxoplasmosis were identified. Conclusion: As parasitic infections pose a problem in a developing country like ours; hence, early detection is always helpful and reduces the morbidity associated with it. Careful assessment of cytological material aspirated from superficial nodules can be very helpful in detecting parasites.